Transformando fósseis em palavras: revitalização da exposição paleontológica do museu paleontológico e arqueológico professor Walter Ilha, São Pedro do Sul, RS - Masetto, Andressa (2020)
The present work addresses the inclusion and accessibility of people with visual or hearing disabilities in paleontology museum spaces, in order to provide access to scientific culture. The 2010 Demographic Census shows that 23.9% of the Brazilian population has some type of disability, and of this percentage, few attend scientific cultural spaces, because they do not know how the service and access will be. Thus, the aim is to adapt and reorganize the paleontological exhibition room at the Professor Walter Ilha Paleontological and Archaeological Museum, in the municipality of São Pedro do Sul, Rio Grande do Sul. For this, the methodology consists on the application of assistive technology (audio description and translation in Libras) accessed via QR Code, labels and information panels in enlarged font, 3D printed Braille labels. This work is important, because the number of museums with paleontological exhibitions, which are accessible and included, is reduced. This proposal will contribute to the protection and dissemination of the local paleontological heritage, in addition to human and cultural heritage valorization.